Pengembangan Gim Edukasi Penggunaan Listrik Bijak Berbasis Android - Joshia Ferdinan Lidwinanta; Harya Bima Dirgantara (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research aims to develop a game titled "Save Energy" that teaches smart electricity usage in an Android-based home. The development of the game employs the Unity 3D Game Engine. The game was created because there are still a large number of people in Indonesia who waste electricity at home. This wastage is the result of a careless culture and a lack of socialization and education. Consequently, the Game Development Life Cycle (GDLC) method is used to create this educational game about saving electricity, with the following stages: initiation, pre-production, production, game testing, and release. This game aims to educate and inform the community about the prudent use of electricity through an engaging and entertaining media game. Users of Android-based smartphones are able to download and play the "Save Energy" video game as a result of its development with this Unity 3D application. After playing this game, as many as 24 individuals can comprehend the prudent use of electricity based on the results of a questionnaire based on the game's trial run.